2020
DOI: 10.1101/2020.11.30.20241133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial disparities in COVID-19 mortality across Michigan, United States

Abstract: Black populations in the US are disproportionately affected by the COVID-19 pandemic, but the increased mortality burden after accounting for health and demographic characteristics is not well understood. We evaluated COVID-19 mortality in Michigan using individual-level death certificate and surveillance data from the Michigan Department of Health and Human Services from March 16 to October 26, 2020. Among the 6,065 COVID-19-related deaths, Black individuals experienced 3.6 times the mortality rate as White i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Compared to Whites, the death rate is 30 to 1, but it has been concluded that the impact is practically significant due to the overall low probability in cases and deaths countrywide. Our research findings are consistent with studies done by [ 16 ] and [ 21 ] which suggest that POC positive cases and death rates were higher in some states but not for the overall country. Specifically, in the District of Columbia, the death rate of Blacks was five times higher than the White ethnic group, while in Michigan, their death rate was three times higher than the White ethnic group [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Compared to Whites, the death rate is 30 to 1, but it has been concluded that the impact is practically significant due to the overall low probability in cases and deaths countrywide. Our research findings are consistent with studies done by [ 16 ] and [ 21 ] which suggest that POC positive cases and death rates were higher in some states but not for the overall country. Specifically, in the District of Columbia, the death rate of Blacks was five times higher than the White ethnic group, while in Michigan, their death rate was three times higher than the White ethnic group [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…While such differences could exist, the county fixed-effects approach ensures our estimates are robust as long as between-race differences in measurement error or reporting lags do not vary substantially over time within counties . Nonetheless, there is limited evidence that timelines between diagnosis, hospitalization, and mortality vary substantially by race [33] , and our analyses ( Figure 1 B) clearly indicate that Black and White COVID-19 mortality surges occur at the same time, suggesting minimal differences by race in both reporting time and mortality.…”
Section: Limitationsmentioning
confidence: 66%
“…Aggregate data containing information of more than two lakh patients with COVID-19 and 14,000 deaths indicate that the male fatality ratio is relatively high compared to the female population among all age groups, particularly middle-aged groups [ 188 ]. Furthermore, Parpia et al have studied the racial disparities among 6065 COVID-19-related deaths in Michigan, USA, and found that in all strata, Black individuals are at higher risk of mortality than White individuals [ 189 ].…”
Section: Degree Of Difference In Cytokines Storm In Relation To Age Sex and Co-morbiditiesmentioning
confidence: 99%